Antioxidant Properties of Essential Oils - Graßmanna, Johanna; Hippelia, Susanne; Dornischa, Kerstin; Rohnerta, Ute; Beuscherb, Norbert; Elstnera, Erich F (Arzneimittelforschung, 2000)
Pathogenesis and symptoms of inflammatory processes are accompanied and/or initiated by the production of reactive oxygen species (ROS). The effects of essential oils on these processes have been studied with the aid of biochemical model reactions simulating these pathological events. It can be shown that Myrtol Standardized and Eucalyptus oil ameliorate inflammatory processes by interacting with agressive oxygen radicals of the OH·-type and interfere with leukocyte activation. These activities partially allow attenuation of oxidative attack and damage introduced by infections or environmental impacts.
Keywords: Eucalyptus oil, antioxidant effects, in vitro studies; Myrtol standardized; Radical scavenging